2014
DOI: 10.1149/2.0851410jes
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Microfluidic Performance of ZnO Surface Acoustic Wave Devices on Various Substrates

Abstract: ZnO thin film-based surface acoustic wave (SAW) devices have been fabricated on Si, glass and polyimide (PI) substrates, and their microfluidic performances were compared. The Rayleigh and Sezawa mode waves were observed from the ZnO/Si devices, the Rayleigh and Lamb modes from the ZnO/PI, and only the Rayleigh mode from the ZnO/glass devices. The ZnO/Si devices have the best performance with the highest acoustic streaming velocity of about 10 cm/s and the shortest particle concentration time of less than 10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“… Comparison of TCF readings between ZnO/Al SAWs in this study and ZnO based SAWs on other commonly used substrates reported in literature 16 , 22 , 23 , 25 , 33 39 . …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“… Comparison of TCF readings between ZnO/Al SAWs in this study and ZnO based SAWs on other commonly used substrates reported in literature 16 , 22 , 23 , 25 , 33 39 . …”
Section: Resultsmentioning
confidence: 81%
“…This could dramatically increase the thermal expansion of the devices during heating/cooling and result in significant variations in the wave velocities with temperature.
Figure 5 Comparison of TCF readings between ZnO/Al SAWs in this study and ZnO based SAWs on other commonly used substrates reported in literature 16 , 22 , 23 , 25 , 33 39 .
…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…ZnO thin film-based surface acoustic wave (SAW) devices have been successfully utilized to fabricate microfluidic pumps. 83,86,89,90 Among different deposition substrates (Si, glass, and polyimides), ZnO deposited on a Si substrate exhibits the highest acoustic streaming velocity of about 10 cm s −1 and the shortest particle concentration time of less than 10 seconds. 90 When introdu-cing ultra-smooth nanocrystalline diamond films with highacoustic wave velocity as an interlayer into a ZnO-based SAW device, the microfluidic efficiency was found to be further enhanced due to reduced acoustic energy dissipation into the Si substrate and improved acoustic properties of SAW devices.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…silicon, glass, metal, or polymer). 7,[10][11][12][13] Currently, piezoelectric thin films such as ZnO have been extensively explored for SAW based sensors and microfluidics. 6,7,14 AlN, another extensively used piezoelectric film materials in microelectro mechanical system (MEMS), has great advantages such as high acoustic velocity, outstanding stability at high temperatures, excellent chemical inertness and good compatibility with CMOS process.…”
Section: Instructionmentioning
confidence: 99%